Composition Effect on the Pore Structure of Transitional Shale: A Case Study of the Permian Shanxi Formation in the Daning–Jixian Block at the Eastern Margin of the Ordos Basin - Zhang, Qin; Qiu, Zhen; Zhao, Qun; Zhang, Leifu; Dong, Dazhong; Wang, Yuman; Hou, Wei; Li, Shuxin; Li, Xingtao (Frontiers in Earth Science, 2022)
Marine–continental transitional (hereinafter referred to as transitional) Permian shales are important targets for shale gas in China because of the considerable volumes of shale gas resources present in them. In this study, transitional shale samples from the Permian Shanxi Formation in the Daning–Jixian block along the eastern margin of the Ordos Basin were collected to investigate the effects of organic and inorganic compositions on the development of their pore structures through organic petrographic analysis, X–ray diffraction, scanning electron microscope (SEM) observation, gas (N2 and CO2) adsorption, high-pressure mercury injection (HPMI), and methane adsorption experiments. The organic petrographic analysis reveals that the Permian Shanxi shale comprises Type-II2-III kerogens, and the average vitrinite reflectance (Ro) is 2.3% at the overmature stage or in the dry gas window. The shale interval at the bottom of the lagoon facies is considered the most favorable interval throughout the entire section because of its high total organic carbon (TOC) content (4.19–43.9%; an average of 16.9%) and high brittle mineral content (38.3–73.2%; an average of 55.8%). N2 and CO2 gas adsorption and HPMI tests reveal the pore size distribution characteristics of the shale. The full pore size distribution by the gas adsorption and HPMI test reveals that micropores (<2 nm) and mesopores (2–50 nm) were dominant in the pore system, and the contributions of the two pore sizes were nearly equivalent, accounting for 21.95–55.05% (an average of 42.3%) and 37.94–64.6% (an average of 49.64%) of the total pore volume, respectively. Additionally, the pore characteristics related to different phases (mainly as silicate, clays, and organic matter) are further clarified by SEM observation and correlation analysis of phase content and pore structure parameters. OM contains numerous SEM-invisible micropores, whereas clay minerals mainly develop mesopores and small macropores (50–100 nm). Furthermore, we calculated the contribution of different shale components to shale porosity. The OM pores account for 0.26–44.1% (an average of 18.7%), and clay mineral pores account for 53.8–93.3% (an average of 76.9%) of the shale porosity. In particular, the OM contributes 73.2% to the surface area and 33.5% to the pore volume. This implies that both OM and clay minerals are important for the storage capacity of adsorbed and free gas.